Emerging nanomedicines for anti-stromal therapy against desmoplastic tumors. (February 2020) - Han, Xuexiang; Xu, Ying; Geranpayehvaghei, Marzieh; Anderson, Gregory J.; Li, Yiye; Nie, Guangjun
Abstract: Solid tumors, especially desmoplastic tumors, are characterized by a dense fibrotic stroma composed of abundant cancer-associated fibroblasts and excessive extracellular matrix. These physical barriers seriously compromise drug delivery to tumor cells, leading to suboptimal treatment efficacy and resistance to current tumor-centric therapeutics. The need to overcome these problems has driven extensive investigations and sparked the flourish of anti-stromal therapy, particularly in the field of nanomedicines. In this paper, we firstly review the major components of the tumor stroma and discuss their impact on drug delivery. Then, according to the different stromal targets, we summarize the current status of anti-stromal therapy and highlight recent advances in anti-stromal nanomedicines. We further examine the potential of nano-enabled anti-stromal therapy to enhance the anti-tumor efficacy of other therapeutic modalities, including chemotherapy, immunotherapy, phototherapy and radiotherapy. Finally, the potential concerns and future developments of anti-stromal nanomedicines are discussed.